Functional assessment of the kidneys in a 10 month‐old child with renal artery stenosis by intravoxel incoherent motion. Issue 3 (March 2017) - Herrmann, Jochen; Ittrich, Harald; Kaul, Michael Gerhard; Groth, Michael; Tozakidou, Magdalini; Blohm, Martin; Oh, Jun; Adam, Gerhard
Abstract: Renovascular stenosis is an important cause for arterial hypertension in childhood. We report a 10‐month‐old girl with arterial hypertension caused by right‐sided renal artery stenosis detected by Doppler ultrasound. Magnetic resonance imaging (MRI) was performed before renal artery angioplasty to depict vascular anatomy in detail and to retrieve additional functional information of the kidneys by analysis of intravoxel incoherent motion (IVIM). The value of quantitative diffusion weighted imaging of the kidneys prior to percutaneous transluminal renal angioplasty (PTRA) is discussed.